Sero-prevalence of unvaccinated adolescent girls susceptible to rubella virus infection seen in a tertiary care hospital of Patna, Bihar, India - Prasad, Dipali; Prasad, Nidhi; Prakash, Vidyut; Parveen, Sadia; Mishra, Urvashi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Rubella infection occurring during early pregnancy results in congenital rubella syndrome (CRS). WHO estimates that worldwide more than 100,000 children are born with CRS each year and most of them are in the developing countries. For assessing population immunity against rubella, sero-surveys are generally recommended among adolescent girls and reproductive age female. In India, sero-surveys conducted by different authors have indicated that about 10-30% of adolescent females are susceptible to rubella infection. Adolescent girls are selected because they are at a critical stage of child bearing age and their immunity against Rubella infection is the particular area of interest. objective of this study was to estimate the sero-prevalence of unvaccinated adolescent girls susceptible to Rubella virus infection attending a tertiary care hospital of Patna and then accordingly counsel for vaccination. Methods: A total 150 adolescent girls in the age group of 10-19 years who had not received MMR vaccine were included in the study. Serum IgG antibody titer for rubella was estimated by the ELISA method. Results: A total 65.33% of the adolescent girls were found to be rubella seropositive and (34.67%) were seronegative. The urban adolescent girls had a higher seropositivity of 85.2% as compared to rural adolescent girls. Conclusions: The study indicates that a substantial number of adolescents (34.67%) are seronegative and hence susceptible to rubella infection.